SCIENTIFIC AND METHODICAL FUNDAMENTALS OF RESTORATION AND ADAPTATION OF BELARUSSIAN HISTORICAL MANORS FOR CULTURAL AND TOURIST USE - N. N. Ulasiuk; G. A. Potaev (Наука и техника)
The executed researches of studying historical manors of Belarus, the analysis of domestic and foreign experience of restoration and modem use of manors have allowed to formulate purposes, principles, conceptual approaches and methods of restoration and adaptation of historical manors for cultural and tourist use.